Edge defect-assisted synthesis of chemical vapor deposited bilayer molybdenum disulfide. Issue 21 (1st November 2021) - Li, Bin; Ju, Qiankun; Hong, Wenting; Cai, Qian; Lin, Jinxin; Liu, Wei
Abstract: The synthesis of two-dimensional molybdenum disulfide (MoS2 ) has invoked much research interest in recent years. In this work, chemical vapor deposition (CVD) was employed to grow a novel molybdenum disulfide. The synthesis reaction was operated in an inert gas environment, with the sulfur precursor placed in the upstream zone of a double zone tube furnace, and the molybdenum trioxide (MoO3 ) precursor placed in a small tube in the downstream zone. A piece of glass was used as the substrate, which was placed beside the small tube. We intentionally built a high concentration of molybdenum precursor above the substrate. The specific morphology hinged highly on the concentration of molybdenum. Abundant molybdenum atoms adsorbed on the edges of the bottom MoS2 and formed defects, which promoted the nucleation of the top layer MoS2 and preferentially grew from the edges. This result provides an innovative method to controllably synthesize novel bilayer molybdenum disulfide by a one-step method of chemical vapor deposition.